Use of Delphi methodology to select sustainability indicators on dairy farms: an exploration of environmental, economic, social and animal welfare dimensions - Sánchez-Hidalgo, Melissa; Tadich, Tamara (Austral Journal of Veterinary Sciences, 2024)
Sustainable livestock production is essential to ensure the availability of food and resources, and to address the social, economic, and environmental challenges that threaten conventional livestock production. While there is consensus among economic, social, and scientific groups on the need to assess sustainability to make decisions that protect resources for present and future generations, there are few sustainability assessment tools that address it holistically. The aim of this study was to develop an assessment tool applicable to farms by identifying the indicators currently applied in dairy farms, based on a systematic literature review and expert opinion. This study used the Delphi methodology to explore sustainability indicators at the farm level. A panel of seven expert researchers and academics in livestock sustainability and animal welfare participated in the study. A high level of consensus was found for 15 economic indicators, 14 social indicators, 20 environmental indicators, and 16 animal welfare indicators. Some indicators, such as financial autonomy, transmissibility, cow and labor productivity, husbandry system, labor intensity, community bonding, labor satisfaction, biodiversity, crop rotation, fertilization, manure management, and water management, showed a high level of consensus and were considered useful in assessing sustainability on dairy farms. In addition, livestock sustainability experts reached a high consensus on 16 animal welfare indicators that could be useful in assessing farm sustainability. These results provide a solid basis for sustainability indicators in the economic, social, environmental, and animal welfare dimensions, which could serve as a basis for developing a sustainability assessment tool for dairy farms.